2019
DOI: 10.5650/jos.ess18176
|View full text |Cite
|
Sign up to set email alerts
|

Oleosome Oil Storage in the Mesocarp of Two Avocado Varieties

Abstract: INTRODUCTION The main feature that distinguishes the avocado fruit Persea americana Mill. is the high content of oil in the mesocarp, which gives the fruit its creamy texture and contributes to its flavor. The oil is a source of saturated palmitic and stearic acid , monounsaturated oleic and palmitoleic acid , and polyunsaturated linoleic and linolenic acid fatty acids that impart health benefits through anticholesterolemic, antioxidant, and anti-inflammatory activities 1 3. Studies on avocado fruit oil have m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…LDs are present in all plant cell types, ranging from a few LDs per cell in leaves to thousands of LDs per cell in seeds ( Kang et al 2022 ). LDs are often referred to in the literature by various terms, for example, lipid bodies, oil bodies, oleosomes or spherosomes depending on the characteristics of the species ( Hsieh and Huang 2004 ; Purkrtova et al 2008 ; Sánchez-Albarrán et al 2019 ; Zienkiewicz and Zienkiewicz 2020 ; Nazari et al 2022 ; Guzha et al 2023 ). These organelles are surrounded by a half membrane and characteristically integrated with specific structural proteins ( Tzen et al 1993 ; Thiam et al 2013 ; Huang 2018 ; Ischebeck et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…LDs are present in all plant cell types, ranging from a few LDs per cell in leaves to thousands of LDs per cell in seeds ( Kang et al 2022 ). LDs are often referred to in the literature by various terms, for example, lipid bodies, oil bodies, oleosomes or spherosomes depending on the characteristics of the species ( Hsieh and Huang 2004 ; Purkrtova et al 2008 ; Sánchez-Albarrán et al 2019 ; Zienkiewicz and Zienkiewicz 2020 ; Nazari et al 2022 ; Guzha et al 2023 ). These organelles are surrounded by a half membrane and characteristically integrated with specific structural proteins ( Tzen et al 1993 ; Thiam et al 2013 ; Huang 2018 ; Ischebeck et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lipid proportions vary among the varieties of avocado, but we focused on the Mexican native variety ( P. americana var. drymifolia) which shows the higher oil content (20–30%) [ 25 ]. The pulp lipids of the native Mexican avocado fruit have attracted attention due to their properties; however, the nutraceutical properties of seed lipids have been poorly studied.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that the difference in size can be related to variety. In the case of avocado, for instance, oleosomes of 41.5 µm were obtained for the Hass variety and 11.9 µm for the americana variety [27]. In future studies, it would be interesting to study the size of the oleosomes of I. gabonensis and correlate them with the variety, butter yield, and even the triglyceride composition.…”
Section: Microscopic Characterization Of I Gabonensis Almondsmentioning
confidence: 98%